Cellular distribution of smooth muscle actins during mammalian embryogenesis: expression of the alpha-vascular but not the gamma- enteric isoform in differentiating striated myocytes (The Rockefeller University Press, 1989)
The cellular distribution of the alpha-vascular and gamma-enteric smooth muscle actin isoforms was analyzed in rat embryos from gestational day (gd) 8 through the first neonatal week by in situ antigen localization using isoactin specific monoclonal antibodies. The alpha-vascular actin isoform was first detected on gd 10 in discrete cells lining the embryonic vasculature. By gd 14, this isoform was also present in the inner layers of mesenchymal cells condensing around the developing airways and gut. The gamma-enteric actin, however, was not detected until gd 15 when cells surrounding the developing aorta, airways, and gut labeled with the gamma-enteric-specific probe. There was continued expression of these two actin isoforms in regions of developing smooth muscle through the remainder of gestation and first neonatal week at which time their distribution coincided with that found in the adult. In addition to developing smooth muscle, the alpha- vascular actin isoform was expressed in differentiating striated muscle cells. On gd 10, there was intense labeling with the alpha-vascular specific probe in developing myocardiocytes and, within 24 h, in somitic myotomal cells. Although significant levels of this smooth muscle actin were present in striated myocytes through gd 17, by the end of the first postnatal week, alpha-vascular actin was no longer detectable in either cardiac or skeletal muscle. Thus, the normal developmental sequence of striated muscle cells includes the transient expression of the alpha-vascular smooth muscle actin isoform. In contrast, the gamma-enteric smooth muscle actin was not detected at any time in embryonic striated muscle. The differential timing of appearance and distribution of these two smooth muscle isoforms indicates that their expression is independently regulated during development.